Shadow Education: Private Supplementary Tutoring Among the Higher Secondary Education in Private Institutions in Agartala - Joel Lalengliana Darlong (International Journal of Integrative Research, 2023)
This study delves in the private tutorial system, commonly known as “shadow education,” since it resembles the mainstream system and is growing at an alarming rate in Tripura. Shadow education appears to have become a permanent presence in certain regions with high-quality systems. Two other variables are the increased competitiveness among pupils to outperform one another and high parental expectations. The rise of shadow education is so rapid that every student has more than one supplemental tutoring or coaching service, which aims to aid kids outside of school, primarily to prepare for exams. This study aims to determine the elements that influence the education system in higher Secondary Schools